Effect of Irrigation Interval on Yield and Yield Components of Two Sugarcane Cultivars Grown at Kenana Sugar Scheme, Sudan - Abdel Wahab, Dafa Alla Mohamed (Gezira Journal of Agricultural Science, 2021)
Field experiments were conducted during 2000/2001 and 2001/2002 at Kenana Sugar Scheme, Sudan ( latitude 13 0 10' N and longitude 32 0 40' E) in heavy clay soils, with 65 % clay, 24% silt, sand and a pH of 7.5-8.5. The objective of the study was to investigate the effects of irrigation intervals (7, 12 and 17 days) on yield and yield components of two sugarcane cultivars: Co 6806 and Co 997. In both experiments, the irrigation treatments were applied three months after sowing. The reference evapotranspiration for Kenana Sugar Scheme was computed using Penman-Monteith approach. The amount of water required for irrigating sugarcane plants was calculated. The results showed that the longest irrigation interval (17 days) led to a decreased cane yield and irrigation water use efficiency, whereas the best cane yield and water use efficiency resulted when irrigating every 12 days followed by every 7 days. The response of the two cultivars was similar under most treatments. However, the cultivar Co 6806 significantly outyielded Co 997 only at 17 days irrigation interval.